ANALISIS KONDISI FISIK PADA ATLET TAEKWONDO POOMSE JUNIOR KABUPATEN KOTABARU - Haikal Lyantama Yogha; Rahmadi; Norma Anggara (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
The purpose of this study is to assess junior poomsae taekwondo athletes in Kotabaru Regency with regard to their physical condition. A quantitative approach using tests and measurements as data collecting methods is the methodology employed. 10 athletes who were chosen based on specific criteria made up the research sample. Speed, flexibility, leg strength, agility, and cardiovascular endurance were among the tests that were employed. The majority of the individuals in this research did